RAPID ADMINISTRATION OF LIFE SAVING DRUGS USING AUTOINJECTORS – DEVELOPMENT OF AMIKACIN AS ANTI BACTERIAL AUTOINJECTOR - R. Vijayaraghavan; R. Selvaraj; S. Krishna Mohan; C.B. Tharani; P. Chattopadhyay; Vijay Veer; A.S.B. Bhaskar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The morbidity and mortality in a number of emergency situations like accidents in civil and military persons can be reduced by immediate administration of drugs. Autoinjector with an antibacterial and an analgesic drug will be very useful for the immediate administration in such situations. These autoinjectors will contain replaceable drug cartridges and are convenient to use by the health care workers with simple instruction.  The drugs will act very fast when delivered by the autoinjectors and intramuscular injection is expected to be equal to intravenous injection due to the forced delivery with a spray effect of the drugs.  Amikacin drug cartridge was developed for the autoinjector and its tolerability was studied in rats by intraperitoneal injection (63 mg).  Rats were given either 3 injections on 3 consecutive days or 7 injections on 7 consecutive days by the autoinjector and compared with manual injection. Blood was withdrawn on the 4th day (3 doses) or the 8th  day (7 doses), and haematological and biochemical parameters viz., WBC, RBC, PCV, Hb, ALT, AST, GGT, LDH, glucose, urea and creatinine were studied. Vital organs viz., lung, liver, spleen, testis, kidney and heart were removed, weighed and preserved for histological studies. All the parameters studied were within the limits and did not show any significant difference when compared with the control. This study showed that intraperitoneal injection of amikacin by the autoinjector designed for intramuscular injection was well tolerated by the rats.